Abstracts (Edited by Prof. Tahir Mahmood) - Mahmood, Tahir (Pakistan Journal of Ophthalmology, 2009)
Effect of phacoemulsification on intraocular pressure in eyes with pseudoexfoliation Single-surgeon series Shingleton BJ, Laul A, Nagao K, Wolff B, Donoghue MO, Eagan E, Flattem N, Desai-Bartoli S, J Cataract Refract Surg 2008; 34: 1834-41 Polypropylene suture-guided valve tube for posterior chamber implantation in patients with pseudophakic glaucoma Moreno-Montafles J, Fantes F, GarcIa-Gomez P J Cataract Refract Surg 2008; 34: 1828-31. Topographically guided laser in situ keratomileusis for myopia using a customized aspherical treatment zone Dougherty PJ, Waring III G, Chayet A, Fischer J, Fant B, Bains BS J Cataract Refract Surg 2008; 34: 1862-71. Corneal elevation and thickness in relation to the refractive status measured with the Pentacam Scheimpflug system Uçakhan Ö Ö, Gesoglu P, Ozkan M, Kanpolat A J Cataract Retract Surg 2008; 34: 1900-5. Anti-vascular endothelial growth factor and retinopathy of prematurity Jonathan E Sears JE Br J Ophthalmol. 2008; 92: 1437-8. Corneal biomechanics, thickness and optic disc morphology in children with optic disc tilt Lim L, Gazzard G, Chan Y-H, Fong A, Kotecha A, Sim E-L, Tan D, Tong L, Saw S-M Br J Ophthalmol 2008; 92: 1461-6